2007
DOI: 10.1158/0008-5472.can-07-2976
|View full text |Cite
|
Sign up to set email alerts
|

3′-Deoxy-3′-[18F]Fluorothymidine Positron Emission Tomography Is a Sensitive Method for Imaging the Response of BRAF-Dependent Tumors to MEK Inhibition

Abstract: Activating mutations of BRAF occur in f7% of all human tumors and in the majority of melanomas. These tumors are very sensitive to pharmacologic inhibition of mitogenactivated protein kinase/extracellular signal-regulated kinase kinase (MEK), which causes loss of D-cyclin expression, hypophosphorylation of Rb, and G 1 arrest. Growth arrest is followed by differentiation or senescence and,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 16 publications
2
42
0
1
Order By: Relevance
“…Melanoma cells appear to repress cellular markers of the melanocytic lineage via activation of the MAPK pathway (24)(25)(26)(27). To some extent, this might reflect a normal developmental process used by melanocytic precursors for lineage determination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melanoma cells appear to repress cellular markers of the melanocytic lineage via activation of the MAPK pathway (24)(25)(26)(27). To some extent, this might reflect a normal developmental process used by melanocytic precursors for lineage determination.…”
Section: Discussionmentioning
confidence: 99%
“…PMEL17 and EDNRB, are suppressed by MAPK signaling (24)(25)(26)(27). As the expression level of a cell surface target can affect the efficacy of an ADC, we evaluated the suitability of combining the anti-EDNRB ADC with the BRAF inhibitors PLX4032 (28) and G590945 and 2 chemically distinct MEK inhibitors GDC-0973 and GDC-0623.…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…Similarly, Shapiro et al reported that PMR was attained in 6 of 15 (40%) evaluable patients treated with a combination of the MEK inhibitor GDC-0973 and the PI3K inhibitor GDC-0941 in a dose-escalation trial (22). 18 F-fluoro-39-deoxy-39-L-fluorothymidine PET to investigate inhibition of proliferation by the MEK inhibitor PD0325901 has also been investigated (23,24). Although several other studies have confirmed the utility of PET in clinical trials, to our knowledge, this was the first study for which 18 F-FDG PET was used in a systematic and consistent manner over 2 phase I clinical trials with a view to comparing 2 compounds with similar mechanisms of action and guiding the most appropriate dose schedule to take forward into phase II.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonspecific incorporation can be observed in proliferating macrophages in inflammatory lesions [8]. It also appears to predict outcome after chemotherapy [9], radiotherapy [10] as well as progression and overall survival of patients with brain tumors [11]. Moreover, in breast cancer [12] and in high-grade non-Hodgkin's lymphoma [13], early change in [ 18 F]FLT uptake, immediately after initiation of chemotherapy predicts tumor response to treatment.…”
Section: Introductionmentioning
confidence: 99%